Compressive Stiffness of Elliptical Leaf Spring Antivibration Mounts - Moussa, L.; Rahman, Muhammad (IRED, 2014)
This paper presents an analytical solution to the in-plane compressive stiffness of elliptical leaf spring anti-vibration mounts (ELS). The accuracy of the proposed solution has been verified with the finite element analysis of the ELS 3D solid model. Parametric analysis conducted to study the effects of transverse shearing, ELS geometry, and compound material properties on the stiffness showed that the transverse shearing has negligible effect and led to the development of useful equations that simplify the determination of the spring stiffness. In addition, it was demonstrated that the stiffness is more sensitive to the outer radius as compared to other design parameters.